ASSOCIATION FACTORS OF DERMATITIS IN THE COASTAL AREAS - Ayukhaliza, Dinda Asa; Damanik, Ananda Ayu Dhelia Ghani; Aisyah, Syafina; Ismah, Zata (LIFE: International Journal of Health and Life-Sciences, 2019)
Dermatitis is a skin disease that affects the quality of life, appearance and comfort of the sufferer. Dermatitis is related to various factors and causes such as infection, consumption of drugs and food, psychosomatic, and exposure to chemicals. The research method used is systematic review with a total sample of 152,996 samples. Risk factors for dermatitis in coastal areas include genetics, type of food, personal hygiene, duration of contact, disease history, years of work, personal protective equipment use, occupational history, protein contact, insect paederus, allergic history, exclusive breastfeeding status, age, education, administration of formula milk, infection and inflammation. The most studied factors are personal hygiene, history of illness and years of work.